Beginning to end hunger : food and the environment in Belo Horizonte, Brazil, and beyond - Chappell, M. Jahi (Michael Jahi) (University of California Press, 2018)
"Beginning to End Hunger presents the story of Belo Horizonte, home to 2.5 million people and the site of one of the world's most successful city food security programs. Since its Municipal Secretariat of Food and Nutritional Security was founded in 1993, malnutrition in Belo Horizonte has declined dramatically, leading it to serve as an inspiration for Brazil's renowned Zero Hunger programs. The Municipal Secretariat's work with local family farmers also offers a glimpse of how food security, rural livelihoods, and healthy ecosystems can be supported together. While inevitably imperfect, Belo Horizonte offers a vision of the path away from food system dysfunction, unsustainability, and hunger. This case study by M. Jahi Chappell shows the vital importance of holistic approaches to food security, offers ideas on how to design successful policies to end hunger, and lays out strategies for making policy change happen. With these tools, we can take the next steps toward achieving similar reductions in hunger and food insecurity elsewhere in the developed and developing worlds."--Provided by publisher.